High-performance buried pipe and preparation method thereof

By using modified crosslinked polyethylene layer and doped β-C3N4 and g-C3N4 composite glass carbon materials in aluminum-plastic composite pipes, the water seepage problem caused by deformation of aluminum-plastic composite pipes is solved, and the strength and resistance of buried pipes are improved. Corrosive, suitable for use in deep geothermal collection areas.

CN119116465AActive Publication Date: 2024-12-13XIN YUAN TAI LI NENG YUAN KE JI (BEI JING) YOU XIAN GONG SI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410980295.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2024-12-13
Estimated Expiration
2044-07-22

AI Technical Summary

Technical Problem

During installation or use, existing aluminum-plastic composite pipes are prone to deformation due to excessive external forces or groundwater and soil impact, resulting in damage or cracks in the aluminum foil layer or aluminum strip layer, which in turn causes water seepage and leakage in the pipeline, and cannot effectively meet the strength and corrosion resistance. Performance requirements.

Method used

A high-performance buried pipe is adopted, which includes a modified crosslinked polyethylene layer, a first modified hot melt adhesive layer, an aluminum alloy layer, a second modified hot melt adhesive layer, and a modified polyethylene layer in sequence from the inside out, and by doping it Miscellaneous β-C3N4 and g-C3N4 composite glass carbon materials improve the strength, corrosion resistance and compressive and seepage resistance of the pipe.

Benefits of technology

It improves the strength and corrosion resistance of the buried pipe, keeps the inner wall smooth, has small fluid resistance, good thermal conductivity, and high heat exchange efficiency. It is suitable for geothermal collection areas with harsh deep geological environment.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a high-performance buried pipe and a preparation method thereof. The high-performance buried pipe sequentially comprises a modified crosslinked polyethylene layer, a first modified hot melt adhesive layer, an aluminum alloy layer, a second modified hot melt adhesive layer and a modified polyethylene layer from inside to outside. The first modified hot melt adhesive layer and the second modified hot melt adhesive layer are both made of polyethylene hot melt adhesive doped with beta-C3N4, the modified crosslinked polyethylene layer is made of crosslinked polyethylene doped with g-C3N4 composite glassy carbon, and the modified polyethylene layer is made of polyethylene doped with g-C3N4 composite glassy carbon. The high-performance buried pipe is high in strength, the inner wall and the outer wall are not prone to corrosion, the inner wall can be kept smooth for a long time, fluid resistance is small, heat conduction performance is good, and heat exchange efficiency is higher. According to the invention, the g-C3N4 is compounded with the glassy carbon, so that the defects caused by independent doping of the g-C3N4 and the glassy carbon are overcome, and the g-C3N4 compounded glassy carbon can be uniformly dispersed in the polyethylene and the crosslinked polyethylene, so that the performance of the pipe is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-performance buried pipe and a preparation method thereof, belonging to the technical field of ground source heat pumps. Background Art

[0002] The ground source heat pump system uses underground soil, groundwater or surface water as energy for heating, cooling or hot water production. Its working principle is similar to that of refrigerant cycle air conditioning, but the difference is that the heat and cold sources it uses are groundwater or ground sources.

[0003] At present, the materials of buried pipes used in ground source heat pumps are usually:

[0004] 1) PVC pipe

[0005] PVC pipes are the most commonly used buried pipe material in ground source heat pumps. They are cheap, durable, resistant to aging, and not easy to deform, but their service life is relatively short, generally 15-20 years.

[0006] 2) PE pipe

[0007] PE pipes have high corrosion resistance, pressure resistance and low temperature resistance, and their service life is generally more than 25 years.

[0008] 3) Aluminum-plastic composite pipe

[0009] Aluminum-plastic composite pipe is a new type of pipe, which has high acid and alkali corrosion resistance, pressure resistance and high temperature resistance. It also has good thermal insulation and heat preservation properties, and its service life is more than 30 years.

[0010] Therefore, for underground pipes with high requirements for strength and corrosion resistance, aluminum-plastic composite pipes are usually selected. The basic structure of aluminum-plastic composite pipes is five layers, namely plastic, hot melt adhesive, aluminum alloy, hot melt adhesive, and plastic from the inside to the outside. However, the existing aluminum-plastic composite pipes have the following defects:

[0011] The aluminum alloy sandwiched in the middle of the aluminum-plastic composite pipe is usually an aluminum foil layer or an aluminum strip layer, which is very thin but has a certain rigidity. If it is excessively deformed due to excessive external force during installation or use, or if it is excessively deformed due to severe groundwater and soil impact, it is easy to damage or crack the aluminum foil layer or the aluminum strip layer, which may cause water seepage and leakage in severe cases.

[0012] Based on this, the present invention is proposed. Summary of the invention

[0013] In view of the shortcomings of the prior art, the present invention provides a high-performance buried pipe and a preparation method thereof. The specific technical scheme is as follows:

[0014] A high-performance buried pipe, comprising, from inside to outside, a modified cross-linked polyethylene layer, a first modified hot-melt adhesive layer, an aluminum alloy layer, a second modified hot-melt adhesive layer, and a modified polyethylene layer;

[0015] The first modified hot melt adhesive layer and the second modified hot melt adhesive layer are both made of polyethylene hot melt adhesive doped with β-C3N4, and the mass fraction of β-C3N4 in the polyethylene hot melt adhesive doped with β-C3N4 is 1.6% to 1.9%;

[0016] The modified cross-linked polyethylene layer is made of cross-linked polyethylene doped with g-C3N4 composite glassy carbon, and the mass fraction of the g-C3N4 composite glassy carbon doped in the cross-linked polyethylene doped with g-C3N4 composite glassy carbon is 7.5% to 9.5%;

[0017] The modified polyethylene layer is made of polyethylene doped with g-C3N4 composite glassy carbon, and the mass fraction of the g-C3N4 composite glassy carbon doped in the polyethylene doped with g-C3N4 composite glassy carbon is 5% to 6%.

[0018] As a further improvement, the mass fraction of the modified cross-linked polyethylene layer in the high-performance buried pipe is 20% to 25%, the mass fraction of the first modified hot-melt adhesive layer in the high-performance buried pipe is 3% to 5%, the mass fraction of the aluminum alloy layer in the high-performance buried pipe is 8% to 12%, and the mass fraction of the second modified hot-melt adhesive layer in the high-performance buried pipe is 3% to 5%.

[0019] As a further improvement, the mass fraction of the modified cross-linked polyethylene layer in the high-performance buried pipe is 21%, the mass fraction of the first modified hot-melt adhesive layer in the high-performance buried pipe is 3.5%, the mass fraction of the aluminum alloy layer in the high-performance buried pipe is 10%, the mass fraction of the second modified hot-melt adhesive layer in the high-performance buried pipe is 3.5%, and the mass fraction of the modified polyethylene layer in the high-performance buried pipe is 62%.

[0020] As a further improvement, the mass fraction of the modified cross-linked polyethylene layer in the high-performance buried pipe is 20%, the mass fraction of the first modified hot-melt adhesive layer in the high-performance buried pipe is 5%, the mass fraction of the aluminum alloy layer in the high-performance buried pipe is 12%, the mass fraction of the second modified hot-melt adhesive layer in the high-performance buried pipe is 5%, and the mass fraction of the modified polyethylene layer in the high-performance buried pipe is 58%.

[0021] As a further improvement, the mass fraction of the modified cross-linked polyethylene layer in the high-performance buried pipe is 25%, the mass fraction of the first modified hot melt adhesive layer in the high-performance buried pipe is 3%, the mass fraction of the aluminum alloy layer in the high-performance buried pipe is 8%, the mass fraction of the second modified hot melt adhesive layer in the high-performance buried pipe is 3%, and the mass fraction of the modified polyethylene layer in the high-performance buried pipe is 61%.

[0022] As a further improvement, the method for preparing the g-C3N4 composite glassy carbon comprises the following steps:

[0023] Pour glassy carbon, g-C3N4 powder and ethanol into a container and mix them, then put the container into an ultrasonic cleaner for ultrasonic dispersion in water, the power of the ultrasonic cleaner is 1250W, the molar ratio of the glassy carbon to the g-C3N4 powder in the container is 0.15:1, the particle size of the glassy carbon is less than or equal to 5μm, and ultrasonic treatment is performed for 1 to 2 hours. After that, the container is placed in a vacuum drying oven for drying at a drying temperature of 79 to 85°C. After drying, the g-C3N4 composite glassy carbon is obtained.

[0024] As a further improvement, the method for preparing the high-performance buried pipe comprises the following steps:

[0025] The high-performance buried pipe is prepared by using an aluminum-plastic composite pipe extruder;

[0026] The modified cross-linked polyethylene layer is prepared by extruding the cross-linked polyethylene doped with g-C3N4 composite glassy carbon as a raw material;

[0027] A first modified hot melt adhesive layer is extruded on the outer wall of the modified cross-linked polyethylene layer using polyethylene hot melt adhesive doped with β-C3N4 as a raw material to obtain a binary composite pipe unit;

[0028] Wrapping the aluminum alloy strip on the outer wall of the binary composite tube unit to obtain the ternary composite tube unit, wherein the aluminum alloy layer is made of the aluminum alloy strip;

[0029] A second modified hot melt adhesive layer is extruded on the outer wall of the ternary composite pipe unit using polyethylene hot melt adhesive doped with β-C3N4 as a raw material to obtain a quaternary composite pipe unit;

[0030] A modified polyethylene layer is extruded on the outer wall of a quaternary composite tube unit using polyethylene doped with g-C3N4 composite glassy carbon as a raw material;

[0031] After extrusion, the high-performance buried pipe is obtained through water cooling.

[0032] Beneficial effects of the present invention:

[0033] 1. The high-performance buried pipe of the present invention has high strength, the inner and outer walls are not easily corroded, the inner wall can remain smooth for a long time, the fluid resistance is small, the thermal conductivity is good, and the heat exchange efficiency is higher.

[0034] 2. The present invention solves the defects caused by doping g-C3N4 and glassy carbon alone by using g-C3N4 composite glassy carbon. The g-C3N4 composite glassy carbon can be evenly dispersed in polyethylene and cross-linked polyethylene, thereby improving the performance of the pipe.

[0035] 3. When the high-performance buried pipe of the present invention is deeply buried, its impact resistance and pressure resistance and anti-seepage properties are effectively improved, and it is particularly suitable for geothermal collection areas in deeper layers and with harsh geological environments. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0037] Example 1

[0038] The high-performance buried pipe comprises, from the inside to the outside, a modified cross-linked polyethylene layer, a first modified hot-melt adhesive layer, an aluminum alloy layer, a second modified hot-melt adhesive layer, and a modified polyethylene layer;

[0039] The first modified hot melt adhesive layer and the second modified hot melt adhesive layer are both made of polyethylene hot melt adhesive doped with β-C3N4, and the mass fraction of β-C3N4 in the polyethylene hot melt adhesive doped with β-C3N4 is 1.6%;

[0040] The modified cross-linked polyethylene layer is made of cross-linked polyethylene doped with g-C3N4 composite glassy carbon, and the mass fraction of the g-C3N4 composite glassy carbon doped in the cross-linked polyethylene doped with g-C3N4 composite glassy carbon is 7.5%;

[0041] The modified polyethylene layer is made of polyethylene doped with g-C3N4 composite glassy carbon, and the mass fraction of the g-C3N4 composite glassy carbon doped in the polyethylene doped with g-C3N4 composite glassy carbon is 5%.

[0042] Among them, the mass fraction of the modified cross-linked polyethylene layer in the high-performance buried pipe is 21%, the mass fraction of the first modified hot melt adhesive layer in the high-performance buried pipe is 3.5%, the mass fraction of the aluminum alloy layer in the high-performance buried pipe is 10%, the mass fraction of the second modified hot melt adhesive layer in the high-performance buried pipe is 3.5%, and the mass fraction of the modified polyethylene layer in the high-performance buried pipe is 62%.

[0043] The preparation method of the g-C3N4 composite glassy carbon comprises the following steps:

[0044] Pour glassy carbon, g-C3N4 powder and ethanol into a container and mix them, then put the container into an ultrasonic cleaner for ultrasonic dispersion in water, the power of the ultrasonic cleaner is 1250W, the molar ratio of the glassy carbon to the g-C3N4 powder in the container is 0.15:1, the particle size of the glassy carbon is less than or equal to 5μm, and ultrasonic treatment is performed for 1h. After that, the container is placed in a vacuum drying oven for drying at a drying temperature of 79-80°C. After drying, the g-C3N4 composite glassy carbon is obtained.

[0045] The method for preparing the high-performance buried pipe comprises the following steps:

[0046] The high-performance buried pipe is prepared by using an aluminum-plastic composite pipe extruder;

[0047] The modified cross-linked polyethylene layer is prepared by extruding the cross-linked polyethylene doped with g-C3N4 composite glassy carbon as a raw material;

[0048] A first modified hot melt adhesive layer is extruded on the outer wall of the modified cross-linked polyethylene layer using polyethylene hot melt adhesive doped with β-C3N4 as a raw material to obtain a binary composite pipe unit;

[0049] Wrapping the aluminum alloy strip on the outer wall of the binary composite tube unit to obtain the ternary composite tube unit, wherein the aluminum alloy layer is made of the aluminum alloy strip;

[0050] A second modified hot melt adhesive layer is extruded on the outer wall of the ternary composite pipe unit using polyethylene hot melt adhesive doped with β-C3N4 as a raw material to obtain a quaternary composite pipe unit;

[0051] A modified polyethylene layer is extruded on the outer wall of a quaternary composite tube unit using polyethylene doped with g-C3N4 composite glassy carbon as a raw material;

[0052] After extrusion, the high-performance buried pipe is obtained through water cooling.

[0053] Example 2

[0054] The high-performance buried pipe comprises, from the inside to the outside, a modified cross-linked polyethylene layer, a first modified hot-melt adhesive layer, an aluminum alloy layer, a second modified hot-melt adhesive layer, and a modified polyethylene layer;

[0055] The first modified hot melt adhesive layer and the second modified hot melt adhesive layer are both made of polyethylene hot melt adhesive doped with β-C3N4, and the mass fraction of β-C3N4 in the polyethylene hot melt adhesive doped with β-C3N4 is 1.8%;

[0056] The modified cross-linked polyethylene layer is made of cross-linked polyethylene doped with g-C3N4 composite glassy carbon, and the mass fraction of the g-C3N4 composite glassy carbon doped in the cross-linked polyethylene doped with g-C3N4 composite glassy carbon is 8%;

[0057] The modified polyethylene layer is made of polyethylene doped with g-C3N4 composite glassy carbon, and the mass fraction of the g-C3N4 composite glassy carbon doped in the polyethylene doped with g-C3N4 composite glassy carbon is 5.5%.

[0058] Among them, the mass fraction of the modified cross-linked polyethylene layer in the high-performance buried pipe is 20%, the mass fraction of the first modified hot melt adhesive layer in the high-performance buried pipe is 5%, the mass fraction of the aluminum alloy layer in the high-performance buried pipe is 12%, the mass fraction of the second modified hot melt adhesive layer in the high-performance buried pipe is 5%, and the mass fraction of the modified polyethylene layer in the high-performance buried pipe is 58%.

[0059] The preparation method of the g-C3N4 composite glassy carbon comprises the following steps:

[0060] Pour glassy carbon, g-C3N4 powder and ethanol into a container and mix them, then put the container into an ultrasonic cleaner for ultrasonic dispersion, the power of the ultrasonic cleaner is 1250W, the molar ratio of the glassy carbon to the g-C3N4 powder in the container is 0.15:1, the particle size of the glassy carbon is less than or equal to 5μm, and ultrasonic treatment is performed for 2h. After that, the container is placed in a vacuum drying oven for drying at a drying temperature of 80-82°C. After drying, the g-C3N4 composite glassy carbon is obtained.

[0061] The method for preparing the high-performance buried pipe comprises the following steps:

[0062] The high-performance buried pipe is prepared by using an aluminum-plastic composite pipe extruder;

[0063] The modified cross-linked polyethylene layer is prepared by extruding the cross-linked polyethylene doped with g-C3N4 composite glassy carbon as a raw material;

[0064] A first modified hot melt adhesive layer is extruded on the outer wall of the modified cross-linked polyethylene layer using polyethylene hot melt adhesive doped with β-C3N4 as a raw material to obtain a binary composite pipe unit;

[0065] Wrapping the aluminum alloy strip on the outer wall of the binary composite tube unit to obtain the ternary composite tube unit, wherein the aluminum alloy layer is made of the aluminum alloy strip;

[0066] A second modified hot melt adhesive layer is extruded on the outer wall of the ternary composite pipe unit using polyethylene hot melt adhesive doped with β-C3N4 as a raw material to obtain a quaternary composite pipe unit;

[0067] A modified polyethylene layer is extruded on the outer wall of a quaternary composite tube unit using polyethylene doped with g-C3N4 composite glassy carbon as a raw material;

[0068] After extrusion, the high-performance buried pipe is obtained through water cooling.

[0069] Example 3

[0070] The high-performance buried pipe comprises, from the inside to the outside, a modified cross-linked polyethylene layer, a first modified hot-melt adhesive layer, an aluminum alloy layer, a second modified hot-melt adhesive layer, and a modified polyethylene layer;

[0071] The first modified hot melt adhesive layer and the second modified hot melt adhesive layer are both made of polyethylene hot melt adhesive doped with β-C3N4, and the mass fraction of β-C3N4 in the polyethylene hot melt adhesive doped with β-C3N4 is 1.9%;

[0072] The modified cross-linked polyethylene layer is made of cross-linked polyethylene doped with g-C3N4 composite glassy carbon, and the mass fraction of the g-C3N4 composite glassy carbon doped in the cross-linked polyethylene doped with g-C3N4 composite glassy carbon is 9.5%;

[0073] The modified polyethylene layer is made of polyethylene doped with g-C3N4 composite glassy carbon, and the mass fraction of the g-C3N4 composite glassy carbon doped in the polyethylene doped with g-C3N4 composite glassy carbon is 6%.

[0074] Among them, the mass fraction of the modified cross-linked polyethylene layer in the high-performance buried pipe is 25%, the mass fraction of the first modified hot melt adhesive layer in the high-performance buried pipe is 3%, the mass fraction of the aluminum alloy layer in the high-performance buried pipe is 8%, the mass fraction of the second modified hot melt adhesive layer in the high-performance buried pipe is 3%, and the mass fraction of the modified polyethylene layer in the high-performance buried pipe is 61%.

[0075] The preparation method of the g-C3N4 composite glassy carbon comprises the following steps:

[0076] Pour glassy carbon, g-C3N4 powder and ethanol into a container and mix them, then put the container into an ultrasonic cleaner for ultrasonic dispersion, the power of the ultrasonic cleaner is 1250W, the molar ratio of the glassy carbon to the g-C3N4 powder in the container is 0.15:1, the particle size of the glassy carbon is less than or equal to 5μm, and ultrasonic treatment is performed for 2h. After that, the container is placed in a vacuum drying oven for drying, the drying temperature is 83-85°C, and the g-C3N4 composite glassy carbon is obtained after drying.

[0077] The method for preparing the high-performance buried pipe comprises the following steps:

[0078] The high-performance buried pipe is prepared by using an aluminum-plastic composite pipe extruder;

[0079] The modified cross-linked polyethylene layer is prepared by extruding the cross-linked polyethylene doped with g-C3N4 composite glassy carbon as a raw material;

[0080] A first modified hot melt adhesive layer is extruded on the outer wall of the modified cross-linked polyethylene layer using polyethylene hot melt adhesive doped with β-C3N4 as a raw material to obtain a binary composite pipe unit;

[0081] Wrapping the aluminum alloy strip on the outer wall of the binary composite tube unit to obtain the ternary composite tube unit, wherein the aluminum alloy layer is made of the aluminum alloy strip;

[0082] A second modified hot melt adhesive layer is extruded on the outer wall of the ternary composite pipe unit using polyethylene hot melt adhesive doped with β-C3N4 as a raw material to obtain a quaternary composite pipe unit;

[0083] A modified polyethylene layer is extruded on the outer wall of a quaternary composite tube unit using polyethylene doped with g-C3N4 composite glassy carbon as a raw material;

[0084] After extrusion, the high-performance buried pipe is obtained through water cooling.

[0085] Comparative Example 1

[0086] The high-performance buried pipe comprises, from the inside to the outside, a cross-linked polyethylene layer, a first hot-melt adhesive layer, an aluminum alloy layer, a second hot-melt adhesive layer, and a polyethylene layer;

[0087] The first hot melt adhesive layer and the second hot melt adhesive layer are both made of polyethylene hot melt adhesive;

[0088] The cross-linked polyethylene layer is made of cross-linked polyethylene;

[0089] The polyethylene layer is made of polyethylene.

[0090] Among them, the mass fraction of the cross-linked polyethylene layer in the high-performance buried pipe is 21%, the mass fraction of the first hot melt adhesive layer in the high-performance buried pipe is 3.5%, the mass fraction of the aluminum alloy layer in the high-performance buried pipe is 10%, the mass fraction of the second hot melt adhesive layer in the high-performance buried pipe is 3.5%, and the mass fraction of the polyethylene layer in the high-performance buried pipe is 62%.

[0091] The method for preparing the high-performance buried pipe comprises the following steps:

[0092] The high-performance buried pipe is prepared by using an aluminum-plastic composite pipe extruder;

[0093] Extruding cross-linked polyethylene as a raw material to form a cross-linked polyethylene layer;

[0094] Using polyethylene hot melt adhesive as raw material, a first hot melt adhesive layer is extruded on the outer wall of the cross-linked polyethylene layer to obtain a binary composite pipe unit;

[0095] Wrapping the aluminum alloy strip on the outer wall of the binary composite tube unit to obtain the ternary composite tube unit, wherein the aluminum alloy layer is made of the aluminum alloy strip;

[0096] Using polyethylene hot melt adhesive as raw material, a second hot melt adhesive layer is extruded on the outer wall of the ternary composite pipe unit to obtain a quaternary composite pipe unit;

[0097] Using polyethylene as raw material, a polyethylene layer is extruded on the outer wall of the quaternary composite pipe unit;

[0098] After extrusion, the high-performance buried pipe is obtained through water cooling.

[0099] Comparative Example 2

[0100] The difference between this example and Example 1 is that in this example, the first modified hot melt adhesive layer and the second modified hot melt adhesive layer are both made of polyethylene hot melt adhesive doped with g-C3N4, and the mass fraction of β-C3N4 in the polyethylene hot melt adhesive doped with g-C3N4 is 1.6%; the rest are the same.

[0101] Comparative Example 3

[0102] The difference between this example and Example 1 is that the modified cross-linked polyethylene layer is made of cross-linked polyethylene doped with g-C3N4 and glassy carbon, g-C3N4 and glassy carbon are not compounded, but directly mixed with the cross-linked polyethylene raw material, the molar ratio of glassy carbon to g-C3N4 powder is 0.15:1, and the rest are the same.

[0103] Comparative Example 4

[0104] The difference between this example and Example 1 is that the modified cross-linked polyethylene layer is made of cross-linked polyethylene doped with β-C3N4 and glassy carbon, β-C3N4 and glassy carbon cannot be compounded, and are directly mixed with the cross-linked polyethylene raw material, and the molar ratio of glassy carbon to β-C3N4 powder is 0.15:1, and the rest are the same.

[0105] Comparative Example 5

[0106] The difference between this example and Example 1 is that the modified polyethylene layer is made of polyethylene doped with g-C3N4 and glassy carbon, g-C3N4 and glassy carbon are not compounded but directly mixed with the polyethylene raw material, the molar ratio of glassy carbon to g-C3N4 powder is 0.15:1, and the rest are the same.

[0107] Comparative Example 6

[0108] The difference between this example and Example 1 is that the glassy carbon in Example 1 is completely replaced by graphene, and the rest is the same.

[0109] Comparative Example 7

[0110] The difference between this example and Example 1 is that the modified cross-linked polyethylene layer is made of cross-linked polyethylene doped with g-C3N4 composite glassy carbon, and the mass fraction of the g-C3N4 composite glassy carbon doped in the cross-linked polyethylene doped with g-C3N4 composite glassy carbon is 9.5%; the rest are the same.

[0111] Comparative Example 8

[0112] The difference between this example and Example 1 is that the modified polyethylene layer is made of polyethylene doped with g-C3N4 composite glassy carbon, and the mass fraction of the g-C3N4 composite glassy carbon doped in the polyethylene doped with g-C3N4 composite glassy carbon is 7%.

[0113] 《Performance Characterization Test of High-Performance Buried Pipe》

[0114] The high-performance buried pipes corresponding to Example 1 and Comparative Examples 1 to 8 were sampled to obtain sample pipes of the same specifications.

[0115] 1. Measure the hydrostatic strength ring stress at 95℃ / 1000h for polyethylene (PE) pipes for water supply according to GB-T-13663-2000.

[0116] 2. Compression and anti-seepage

[0117] 2.1. Perform the first pressure test on the sample tube. The water pressure in the sample tube is 0.6MPa. Maintain the pressure for 15 minutes and check for leaks.

[0118] 2.2. The sample tube is flattened in the radial direction under the press, and the flattening rate is 25% (for example, the outer diameter of the sample tube is 36 mm, and the minimum outer diameter of the sample tube after flattening is 27 mm). The flattened sample tube is then restored to its original state under normal pressure, which is one flattening action. After repeating the flattening action 1000 times, the sample tube is pressure tested for the second time, and the water pressure in the sample tube is 0.6 MPa. The pressure is maintained for 15 minutes to check for leakage. If there is leakage, the water leaked within 15 minutes of stable pressure is collected and weighed. The total weight of the leaked water can reflect the anti-seepage performance of the sample tube after high-frequency flattening test. The results are shown in Table 1.

[0119] Table 1

[0120] 95℃ / 1000hHydrostatic strength ring stress First pressure test Second pressure test Example 1 3.57MPa No leakage No leakage Comparative Example 1 3.02MPa No leakage Total weight of leaked water: 3.5kg Comparative Example 2 3.09MPa No leakage Total weight of leaked water: 2.1kg Comparative Example 3 2.89MPa No leakage The total weight of the leaked water is 4.7kg Comparative Example 4 2.83MPa No leakage Total weight of leaked water: 5.5kg Comparative Example 5 2.51MPa No leakage Total weight of leaked water: 4.3kg Comparative Example 6 3.50MPa No leakage Total weight of leaked water: 1.2kg Comparative Example 7 3.53MPa No leakage Total weight of leaked water: 0.8kg Comparative Example 8 3.55MPa No leakage No leakage

[0121] It can be seen from Table 1 and Comparative Example 2 that in polyethylene hot melt adhesive, doping light-weight g-C3N4 alone can easily lead to uneven mixing. Although it does not help to improve the impact resistance (95°C / 1000h hydrostatic strength ring stress), it will significantly affect its compressive and impermeability. During multiple extrusion deformation processes, it is very easy to cause microcracks in the pipe, resulting in leakage.

[0122] It can be seen from Table 1 and Comparative Example 3 that if g-C3N4 and glassy carbon are doped separately in the inner tube (modified cross-linked polyethylene layer), due to the hardness of the material and the uneven distribution of the doped hard particles (fillers), it will lead to a decrease in impact resistance and compressive and impermeability properties.

[0123] It can be seen from Table 1 and Comparative Example 4 that if the inner tube (modified cross-linked polyethylene layer) is doped with β-C3N4 and glassy carbon with higher hardness, due to its hardness and the uneven distribution of the doped hard particles (fillers), it will lead to a decrease in impact resistance and compressive and impermeability properties.

[0124] It can be seen from Table 1 and Comparative Example 5 that if lightweight g-C3N4 and glassy carbon are doped alone in the outer tube (modified polyethylene layer), the hard nature of g-C3N4 and the difficulty in uniformly dispersing it will easily lead to uneven distribution of the doped particles (fillers), which will in turn lead to a decrease in impact resistance and compression and impermeability, and will have a greater impact on impact resistance.

[0125] From Table 1 and Comparative Example 6, it can be seen that the composite of g-C3N4 and graphene has little effect on the strength of polyethylene and cross-linked polyethylene, so the impact resistance does not change much. However, its improvement in toughness is not as good as glassy carbon, so it will cause a decrease in both compressive and impermeability resistance.

[0126] It can be seen from Table 1 and Comparative Example 7 that if the content of g-C3N4 composite glassy carbon in the inner tube (modified cross-linked polyethylene layer) is too large, the impact resistance will not change much, but will lead to a decrease in both compression resistance and anti-permeability.

[0127] It can be seen from Table 1 and Comparative Example 8 that if the content of g-C3N4 composite glassy carbon in the outer tube (modified polyethylene layer) is too large, the impact resistance and the compressive and impermeability resistance will not change much.

[0128] In the above embodiment, the polyethylene hot melt adhesive doped with β-C3N4 can be obtained by mixing β-C3N4 powder in the polyethylene hot melt adhesive raw material; the cross-linked polyethylene doped with g-C3N4 composite glassy carbon can be obtained by mixing g-C3N4 composite glassy carbon in the cross-linked polyethylene raw material. The polyethylene doped with g-C3N4 composite glassy carbon can be obtained by mixing g-C3N4 composite glassy carbon in the polyethylene raw material.

[0129] Polyethylene hot melt adhesive was purchased from Kangkai Renewable Resources Recycling Co., Ltd., Congtai District, Handan City.

[0130] In the present invention, g-C3N4 composite glassy carbon is used to solve the defects caused by doping g-C3N4 and glassy carbon alone. The g-C3N4 composite glassy carbon can be evenly dispersed in polyethylene and cross-linked polyethylene, thereby improving the performance of the pipe.

[0131] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-performance buried pipe, characterized in that: From the inside to the outside, it includes a modified cross-linked polyethylene layer, a first modified hot melt adhesive layer, an aluminum alloy layer, a second modified hot melt adhesive layer, and a modified polyethylene layer. The first modified hot melt adhesive layer and the second modified hot melt adhesive layer are both made of polyethylene hot melt adhesive doped with β-C3N4, and the mass fraction of β-C3N4 in the polyethylene hot melt adhesive doped with β-C3N4 is 1.6% to 1.9%; The modified cross-linked polyethylene layer is made of cross-linked polyethylene doped with g-C3N4 composite glassy carbon, and the mass fraction of the g-C3N4 composite glassy carbon doped in the cross-linked polyethylene doped with g-C3N4 composite glassy carbon is 7.5% to 9.5%; The modified polyethylene layer is made of polyethylene doped with g-C3N4 composite glassy carbon, and the mass fraction of the g-C3N4 composite glassy carbon doped with the g-C3N4 composite glassy carbon in the polyethylene doped with g-C3N4 composite glassy carbon is 5% to 6%.

2. A high performance buried pipe according to claim 1, characterized in that: The mass fraction of the modified cross-linked polyethylene layer in the high-performance buried pipe is 20% to 25%, the mass fraction of the first modified hot-melt adhesive layer in the high-performance buried pipe is 3% to 5%, the mass fraction of the aluminum alloy layer in the high-performance buried pipe is 8% to 12%, and the mass fraction of the second modified hot-melt adhesive layer in the high-performance buried pipe is 3% to 5%.

3. A high performance buried pipe according to claim 2, characterized in that: The mass fraction of the modified cross-linked polyethylene layer in the high-performance buried pipe is 21%, the mass fraction of the first modified hot-melt adhesive layer in the high-performance buried pipe is 3.5%, the mass fraction of the aluminum alloy layer in the high-performance buried pipe is 10%, the mass fraction of the second modified hot-melt adhesive layer in the high-performance buried pipe is 3.5%, and the mass fraction of the modified polyethylene layer in the high-performance buried pipe is 62%.

4. A high performance buried pipe according to claim 2, characterized in that: The mass fraction of the modified cross-linked polyethylene layer in the high-performance buried pipe is 20%, the mass fraction of the first modified hot-melt adhesive layer in the high-performance buried pipe is 5%, the mass fraction of the aluminum alloy layer in the high-performance buried pipe is 12%, the mass fraction of the second modified hot-melt adhesive layer in the high-performance buried pipe is 5%, and the mass fraction of the modified polyethylene layer in the high-performance buried pipe is 58%.

5. The high-performance buried pipe according to claim 2, characterized in that: The mass fraction of the modified cross-linked polyethylene layer in the high-performance buried pipe is 25%, the mass fraction of the first modified hot-melt adhesive layer in the high-performance buried pipe is 3%, the mass fraction of the aluminum alloy layer in the high-performance buried pipe is 8%, the mass fraction of the second modified hot-melt adhesive layer in the high-performance buried pipe is 3%, and the mass fraction of the modified polyethylene layer in the high-performance buried pipe is 61%.

6. The high-performance buried pipe according to claim 1, characterized in that: The preparation method of the g-C3N4 composite glassy carbon comprises the following steps: Pour glassy carbon, g-C3N4 powder and ethanol into a container and mix them, then put the container into an ultrasonic cleaner for ultrasonic dispersion in water, the power of the ultrasonic cleaner is 1250W, the molar ratio of the glassy carbon to the g-C3N4 powder in the container is 0.15:1, the particle size of the glassy carbon is less than or equal to 5μm, and ultrasonic treatment is performed for 1 to 2 hours. After that, the container is placed in a vacuum drying oven for drying at a drying temperature of 79 to 85°C. After drying, the g-C3N4 composite glassy carbon is obtained.

7. A method for preparing a high-performance buried pipe according to any one of claims 1 to 6, characterized in that: The following steps are involved: The high-performance buried pipe is prepared by using an aluminum-plastic composite pipe extruder; The modified cross-linked polyethylene layer is prepared by extruding the cross-linked polyethylene doped with g-C3N4 composite glassy carbon as a raw material; A first modified hot melt adhesive layer is extruded on the outer wall of the modified cross-linked polyethylene layer using polyethylene hot melt adhesive doped with β-C3N4 as a raw material to obtain a binary composite pipe unit; Wrapping the aluminum alloy strip on the outer wall of the binary composite tube unit to obtain the ternary composite tube unit, wherein the aluminum alloy layer is made of the aluminum alloy strip; A second modified hot melt adhesive layer is extruded on the outer wall of the ternary composite pipe unit using polyethylene hot melt adhesive doped with β-C3N4 as a raw material to obtain a quaternary composite pipe unit; A modified polyethylene layer is extruded on the outer wall of a quaternary composite tube unit using polyethylene doped with g-C3N4 composite glassy carbon as a raw material; After extrusion is completed and water-cooled, the high-performance buried pipe is obtained.

Citation Information

Patent Citations

  • Method for processing low-temperature-resistant aluminum-plastic composite pipe

    CN108329555A

  • Multi-layer composite pipe for thermal management system of new energy automobile and preparation process thereof

    CN112576822A

  • Pipe Jointer made of refractory non-cross-linked polyethylene and cross-linked polyethylene

    CN1391058A